Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s0168-6496(03)00160-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil improvement treatments on bacterial community structure and soil processes in an upland grassland soil

Abstract: Temporal temperature gradient electrophoresis (TTGE) analysis of 16S rRNA gene fragments amplified with primers selective for eubacteria and beta-proteobacterial ammonia-oxidising bacteria (AOB) was used to analyse changes in bacterial and AOB community profiles of an upland pasture following soil improvement treatments (addition of sewage sludge and/or lime). Community structure was compared with changes in activity assessed by laboratory measurements of basal respiration and ammonia oxidation potentials, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 34 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Composition was highly variable over seasons and years, and compositional changes in response to the nutrient treatments were minor in comparison. High temporal variability in AOB communities (both abundance and composition) has been observed in both soils and the water column (Gray et al, 2003;O'Mullan and Ward, 2005) and in estuarine sediments (Bernhard et al, 2007;Ando et al, 2009;Fortunato et al, 2009). Given the importance of temperature on the spatial variability of AOB in soils (Fierer et al, 2009), we speculate that temperature could be one important factor contributing to this temporal variability.…”
Section: Temporal Variability and Nutrient Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…Composition was highly variable over seasons and years, and compositional changes in response to the nutrient treatments were minor in comparison. High temporal variability in AOB communities (both abundance and composition) has been observed in both soils and the water column (Gray et al, 2003;O'Mullan and Ward, 2005) and in estuarine sediments (Bernhard et al, 2007;Ando et al, 2009;Fortunato et al, 2009). Given the importance of temperature on the spatial variability of AOB in soils (Fierer et al, 2009), we speculate that temperature could be one important factor contributing to this temporal variability.…”
Section: Temporal Variability and Nutrient Responsesmentioning
confidence: 88%
“…Once they accounted for this variability statistically, however, they could detect a correlation between contaminant concentrations and bacterial composition. Similarly, Gray et al (2003) determined that soil amendments had a minor effect on eubacterial (and AOB) composition relative to natural, temporal and spatial variability.…”
Section: Temporal Variability and Nutrient Responsesmentioning
confidence: 99%
“…The mechanism is unknown but both are direct effects of fertilizer itself, and changes in the plant community and litter associated with fertilizers could be involved (Donnison et al 2000;Manning et al 2006). Fungal DNA profiles can also undergo a reduction in diversity in response to fertilizer (Allison et al 2007), but others found that the bacterial communities (but not fungi) can be altered by high rates of fertilizer (Gray et al 2003;Kennedy et al 2004Kennedy et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although different phylotypes arose in different replicates, their performances in these systems were similar enough to result in communities whose functions were indistinguishable from each other. This implies a substantial degree of functional redundancy in these microbial communities, as has been found in a variety of natural and engineered microbial ecosystems (2,10,22,38,45). One rationale for the emphasis on analysis of microbial community composition in microbial ecology has been that determining composition is key to understanding community functionality.…”
Section: Discussionmentioning
confidence: 99%